DESENTRALISASI FISKAL DAN MANAJEMEN ANGGARAN DAERAH: STUDI DI JAWA TIMUR - Khusaini, Moh. (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2007)
Indonesia has implemented a new era of fiscal decentralization and regionalautonomy since January 2001. One important aspect of fiscal decentralization isgood governance, public budgeting management, and decentralization ofgovernment functions in lower level leads to achieve efficiency in allocating publicgoods despite differences in preferences of regions. This research aims at analyzingthe influence of fiscal decentralization on public budgeting management especiallycase of District and City in East Java Province. There is an argument thatdecentralization can improve the quality of governance and public services bybringing government closer to people. By using descriptive analysis and literaturereview indicated that fiscal decentralization in Indonesia was not fully consistent inexplaining theory of fiscal decentralization. The impact of fiscal decentralization topublic budgeting management indicated that there was greater nominal change onlocal budget. However, the allocation of public budget for basic services were verylow and still far from transparency, accountability, and efficiency. This findings alsoindicated that local budget were not really public oriented yet.Keywords: fiscal decentralization, good governance, public budgeting management